(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2010)
The following study is considered as a part of the requests of reconstructing a strategy to develop Al-Hamza city (urban center)and to put to a plan to renew the basic design of the city center, this will participate in establishing a primary data base beside the urban planning to assist for the base imagination about the capabilities and limitations of the development in order to establish a strategy of development of Al-Hamza city in the hands of the wanted basic planning . This study depended on different references, historical academic and statistics in addition to number of field-visits to the region and listening to the points of views of the local peoples and establishing interviews to the local habitants of the area especially those heads of the tribes and the city- center gentlemen in order to add the documentary and scientific interests and to discover some of the service needs that can be depended to start the stage of preparing the requests of plan of the development and reconstruction of renewing urban planning of land uses. In this level of study it has been worked to discover the planning signs via specifying the capabilities and chances on which the city-planning strategy can be built in addition to prepare substitutes for the new basic design ,of the most important results are studying the population statistics and its expected population numbers under the balance between the people on our side and what the city needs of the services according to the present and expected offer and the available need and defect in the services .